THE EFFECTIVENESS OF DISCOVERY LEARNING WITH TRUTH OR DARE TECHNIQUE IN IMPROVING STUDENTS' LOGICAL THINKING ABILITY - Royyan Arifin; Edi Irawan (INSECTA: Integrative Science Education and Teaching Activity Journal, 2020)
This research originated from a phenomenon that shows the low ability of students to think logically. This study aims to provide solutions to improve students' logical thinking skills by using discovery learning with truth or dare techniques. This type of research is a quasi-experimental design with a two-group pretest-posttest. The data were collected using a pre-test and post-test of students' logical thinking skills. The population in this study were students of class VII SMPN 5 Ponorogo. Those who were randomly selected as samples were class VII-F as the experimental class and class VII-I as the control class. Furthermore, data analysis was performed using the t-test. The results showed that the effectiveness of the discovery learning model of truth or dare learning technique with conventional learning has a significant difference. The ability to think logically between students who use the Discovery Learning learning model truth or dare technique is higher than the logical thinking skills of students who use conventional learning. The use of this learning model provides the opportunity for students to find concepts related to the material independently. As a result, students can hone and optimize their logical thinking skills to solve the problems they face during the learning process.